2018
DOI: 10.1002/jum.14580
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Thyroid Carcinoma Recurrence: Low Yield of Neck Ultrasound With an Undetectable Serum Thyroglobulin Level

Abstract: Neck US did not identify recurrent PTC when the serum Tg level was undetectable in patients who underwent total thyroidectomy and RAI therapy. Eliminating neck US when serum TG levels are undetectable could decrease unnecessary imaging examinations without negatively affecting the ability to detect recurrent disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…However, we considered it a false positive finding, as the subsequent neck US was normal. This result is consistent with previous studies that showed high rates of false positives from neck USs ( 12 - 14 ) and low probability of detecting clinically relevant structural recurrence ( 12 - 16 , 24 ). Moreover, a recent study by Sek and cols.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, we considered it a false positive finding, as the subsequent neck US was normal. This result is consistent with previous studies that showed high rates of false positives from neck USs ( 12 - 14 ) and low probability of detecting clinically relevant structural recurrence ( 12 - 16 , 24 ). Moreover, a recent study by Sek and cols.…”
Section: Discussionsupporting
confidence: 93%
“…Three recently conducted studies reported false-positives in 67% ( 12 ), 57% ( 13 ) and 43.9% ( 14 ) of the patients, but only 1.2% ( 12 ) to 10% ( 13 ) of patients had a true recurrence. Similarly, two other studies have shown that a routine neck US for patients with reduced risk of recurrence has a very low probability of identifying recurrence ( 15 , 16 ), even if initially suspicious findings were detected ( 16 ).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In this study, 8.3 % of patients in the image group had cervical structural disease during follow-up. Nonspecific lesions can be difficult to distinguish between recurrent thyroid cancer and non-recurrent benign lesions with neck US alone [18][19][20][21][22]. Recent studies have proposed to restrict US to patients with basal Tg ≥ 1 ng/ml after treatment with RAI because this imaging method revealed ▶Fig.…”
Section: Discussionmentioning
confidence: 99%